Culturally framing 'safe sport': on political mobilisation against abuse in Zambian sport. Issue 4 (2nd October 2019) - Solstad, Gerd Marie; Strandbu, Åse
ABSTRACT: Formalisation of safeguarding in sport occurs in increasingly diverse contexts to address abuse of athletes and promote 'safe sport'. Moreover, safeguarding policies are occasionally integrated in transnational Sport for Development (SfD) partnerships as a condition for funding. In this article, we draw from social movement theory to explore political mobilisation against abuse in Zambian sport associations that have a Norwegian SfD partner. Using the concept of 'cultural framing', we examine how safe sport is captured, presented and understood by coaches and sport leaders involved in Zambian sport. The analysis shows that there was considerable support for formalised safeguarding, even though ambivalence was expressed regarding the extent of abuse in sport. With motivation grounded in resonance with sport priorities and humanistic values, safeguarding seemingly equipped the sport associations with a practicable formula for confronting a morally evocative problem. Coupled with a strong network of local mobilising actors championing this cause and a conducive political climate for connecting sport with broader social responsibilities, we suggest that this cultural framing facilitated political mobilisation against abuse in Zambian sport. Lastly, we outline some implications of our findings for safeguarding in sport and for the politicisation of sport issues.